2005
DOI: 10.2134/jeq2005.0717
|View full text |Cite
|
Sign up to set email alerts
|

Cascading Ecological Effects of Low‐Level Phosphorus Enrichment in the Florida Everglades

Abstract: Few studies have examined long-term ecological effects of sustained low-level nutrient enhancement on wetland biota. To determine sustained effects of phosphorus (P) addition on Everglades marshes we added P at low levels (5, 15, and 30 microg L(-1) above ambient) for 5 yr to triplicate 100-m flow-through channels in pristine marsh. A cascade of ecological responses occurred in similar sequence among treatments. Although the rate of change increased with dosing level, treatments converged to similar enriched e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 21 publications
14
75
2
Order By: Relevance
“…A similar response has been described for other oligotrophic, P-limited wetlands such as the Florida Everglades (McCormick et al 1996(McCormick et al , 1998Gaiser et al 2005). While autotrophic cyanobacteria were eliminated, the biomass of heterotrophic sediment microorganisms increased due to higher C, input, as documented by increase in total organic C and, consequently, in microbial C, and total PLFA.…”
Section: Discussionsupporting
confidence: 75%
“…A similar response has been described for other oligotrophic, P-limited wetlands such as the Florida Everglades (McCormick et al 1996(McCormick et al , 1998Gaiser et al 2005). While autotrophic cyanobacteria were eliminated, the biomass of heterotrophic sediment microorganisms increased due to higher C, input, as documented by increase in total organic C and, consequently, in microbial C, and total PLFA.…”
Section: Discussionsupporting
confidence: 75%
“…Our data indicated that while nutrient loading to WCA-3 has affected a smaller percentage of the area of WCA-3 than WCA-2A, the total area of WCA-3 with TPm > 500 mg kg −1 in both 1992 and 2003 was greater than the total area of WCA-2A with TPm > 500 mg kg −1 in 1998. Slowing the increase of soil TPm in WCA-3 is even more critical in light of recent research that has shown that soils respond more slowly to elevated TP than other ecosystem components such as periphyton, floc, and plants Gaiser et al, 2005).…”
Section: Geostatistical Analysesmentioning
confidence: 99%
“…To inform such restoration efforts, various authors have been studying the effects of drying frequency on mat primary production [42,43] and on nutrient fluxes in plant and algal communities [29,31,44,45 Figure 1) and randomly assorted into 72 beakers (400 mL) that were kept in cool, dark conditions until the start of the experiment. The mats in this region are representative of the "short-hydroperiod" (6-9 months flooding duration and more than one wet-dry cycle per year) of the upstream areas of the TS/Ph and SRS drainages [25,32]. The area was flooded at the time of sampling.…”
Section: Study Regionmentioning
confidence: 99%